2016
DOI: 10.1063/1.4959783
|View full text |Cite
|
Sign up to set email alerts
|

Electrical four-point probing of spherical metallic thin films coated onto micron sized polymer particles

Abstract: Micron-sized metal-coated polymer spheres are frequently used as filler particles in conductive composites for electronic interconnects. However, the intrinsic electrical resistivity of the spherical thin films has not been attainable due to deficiency in methods that eliminate the effect of contact resistance. In this work, a four-point probing method using vacuum compatible piezo-actuated micro robots was developed to directly investigate the electric properties of individual silvercoated spheres under real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In reality, 𝜌 deviates from the bulk value due to impurities or thickness and grain size constraints in thin metal coatings [11]. Additionally, t may be inhomogeneous within one MPS and varies from particle to particle [5]. The first four-point resistivity measurements on individual micron-sized particles were reported by Sun et al [12].…”
Section: Single Particle Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In reality, 𝜌 deviates from the bulk value due to impurities or thickness and grain size constraints in thin metal coatings [11]. Additionally, t may be inhomogeneous within one MPS and varies from particle to particle [5]. The first four-point resistivity measurements on individual micron-sized particles were reported by Sun et al [12].…”
Section: Single Particle Resistancementioning
confidence: 99%
“…In previous works, two methodologies have been used to investigate electrical properties of individual MPS. Electromechanical nanoindentation has been used to measure the electrical resistance of single MPS under compression [4], while four-point probe measurements directly on MPS were used to determine the resistivity of the metal coating [5]. In a continuation of these works, we present an improved method of determining the coating resistivity of MPS, and apply these measurements to further interpret electromechanical nanoindentation data.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the intrinsic conductivities of the spherical silver thin films are lower than that of bulk silver. 10 This is mainly caused by increased electron scattering at grain boundaries as the grains become smaller than the electron mean free path of bulk silver, as well as possible impurities form the electroless plating process used to coat the polymer spheres with the silver thin films, and can even result in thicker films exhibiting lower intrinsic conductivities than thinner films. 10 The silver…”
Section: E Thermal Conductivitymentioning
confidence: 99%
“…% silver, 7,8 and the mechanisms controlling the electrical properties of these conductive composites are starting to be clarified. [8][9][10][11] However, investigation of the thermal properties of AgPS-based ICAs have been sparse, and to our best knowledge, only one paper has been published on the subject to date. 7 The mechanisms controlling the thermal transport of these ICAs are still largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to guided or self-assembly technology, observation and laser aiming for optical trapping is time-consuming, and regarding particle moving is individually performed, which results in size limitation of processing area although usage of galvo-scanner accelerates arrangement process for particular applications [16]. Besides, fast arrangement of particles over large-area is also challenging for mechanical positioning methods which typically use probe of Atomic Force Microscopy (AFM) or piezo-based robotic manipulator to push particles to targeted positions [17,18].…”
Section: Introductionmentioning
confidence: 99%